Gamification for Enhancing Students’ Interest in Learning English: A Survey on the Role of Quizizz at MTsN 4 Sidoarjo - Akbar, Muhammad Ramadhandiati; Imaniar, Fahmy; Yaqin, Nurul (ICONELT, 2024)
Since Quizizz appeared and became a web-based learning platform, MTsN 4 Sidoarjo are used for learning English in class using Quizizz as a Gamification. Quizizz has a variety of features for learning english activity at MTsN 4 Sidoarjo such as multiplayer activities, interactive quizzes, avatars, themes, memes, and music to make learning more engaging and dynamic. Quizizz uses game-like elements such as points, leaderboards, and rewards to make learning more enjoyable and competitive. This study investigates students’ and teachers’ perceptions of using Quizizz web-based learning as a popular learning platform, in English language teaching (ELT) at MTs Negeri 4 Sidoarjo. A qualitative research design was employed, involving the distribution of an observation, interview and focus group discussion to 10 students and English Teacher in class 7 A & 7 G. The findings reveal that the majority of students found Quizizz to be an engaging and Fun tool for learning English speaking, reading, listening, writing and other language skills. Specific features that engaged students while using this platform such as Leaderboards, Meme Feedback and Music Options, and Question Timers. The study highlights the potential of using Quizizz and interactive learning platforms to create immersive and enjoyable learning experiences, fostering curiosity and a deeper connection with the subject matter. Recommendations for future research include investigating the long-term impact on academic performance, knowledge retention, and the effectiveness of such platforms across different age groups and learning styles.